Behavioral Orientation of Muslim Voters in the 2024 Gubernatorial Election in East Nusa Tenggara Province - Gai, Apolonaris; ., Kushandajani; Alfirdaus, Laila Kholid; Herawati, Nunik Retno (Journal of Posthumanism, 2025)
This study, entitled “Behavioral Orientation of Muslim Voters in the 2024 Gubernatorial Election in East Nusa Tenggara”, aims to analyze the orientation of Muslim voters’ behavior through sociological, psychological, and rational approaches and to identify the dominant factors influencing voters’ considerations in selecting candidates for Governor and Vice Governor in the 2024 election in East Nusa Tenggara. This research employs a mixed-methods approach with an exploratory type and a sequential model. The findings reveal that, from a sociological perspective, Muslim voters in the 2024 East Nusa Tenggara election are influenced by social factors such as age, gender, region, ethnicity, and the influence of political figures. Voters tend to prefer candidates with a strong track record, integrity, and credibility, although religious identity also plays a role in decision-making. From a psychological perspective, voters favor candidates over party identity, showing high recognition of major parties such as Gerindra (80%), PDIP (80%), and Golkar (88%). Voters tend to support parties with ideological and historical proximity, such as PKB and Golkar. The voters focus on social, economic, and political issues, prioritizing poverty, education, healthcare, and corruption. Muslim voters’ preferences in the 2024 gubernatorial election lean toward Benny K. Harman (24%) and Melki Laka Lena (23%). Interviews with community leaders reveal that support is influenced by religious identity, political experience, and the influence of senior figures. From a rational approach, key issues that candidates must address include poverty, unemployment, limited job opportunities, and corruption. Voters prioritize economic issues (97%), followed by healthcare and education (93%), and anti-corruption efforts. The most dominant factor influencing voter behavior is candidate personal attributes (93%), followed by the candidate’s educational background (61%). Although religion and ethnicity still play a role, they are less influential than candidate qualities and education. In conclusion, based on the sociological approach, Muslim voters focus on practical change, especially those with lower educational backgrounds. The psychological approach shows that voters are becoming more critical of religious symbols, emphasizing concrete policies and candidate integrity. The rational approach highlights the primary issues in the 2024 gubernatorial election: education, healthcare, economy, social welfare, infrastructure, and interreligious tolerance.